PENGARUH KEPEMILIKAN MANAJERIAL, KEPEMILIKAN INSTITUSIONAL, DAN KEPEMILIKAN PEMEGANG SAHAM BLOK TERHADAP BIAYA AGENSI PADA PERUSAHAAN NON-KEUANGAN DI BURSA EFEK INDONESIA (BEI) - Rifka Devi; Faisal Faisal (Jurnal Ilmiah Mahasiswa Ekonomi Manajemen, 2021)
This study aims to determine the effect of managerial ownership, institutional ownership, and block shareholder ownership on agency costs in non-financial companies on the Indonesia Stock Exchange (BEI). This study uses panel data with 23 non-financial companies listed on the Indonesia Stock Exchange from 2013-2018. The data analysis method used is multiple regression analysis with a fixed effect model. The results of the study partially show that managerial ownership has a negative and insignificant effect on agency costs, institutional ownership has a positive and significant effect on agency costs. agency costs and block shareholder ownership have a negative and significant effect on agency costs. The results showed that managerial ownership, institutional ownership, and block shareholder ownership had a positive effect on agency costs simultaneously